The English Print Trade in the Reign of Edward VI, 1547–1553 - Richards, Celyn David, author.
1 online resource (310 pages)
Keywords: The protestant reformation was critical to the efflorescence of printing in England between 1547 and 1553. Celyn David Richards explores English print culture during this turbulent period, as an official programme of reform, new censorship dynamics and increasingly sophisticated commercial relationships contributed to the trade’s rapid expansion. Edward VI’s reign saw unprecedented levels of religious print production, London’s first publishing syndicate, and a climate of protestant ascendancy which helped English print culture to make up ground on its continental counterparts.